The Wasilah with Stones as Media in Samadiyah Tradition in Peulokan Village of West Labuhan Haji District, South Aceh (TAFSE: Journal of Qur'anic Studies, 2023)
The wasilah tradition practiced by community members of Peulokan village, West Labuhan Haji in South Aceh, is different from the others which used stones as media of wasilah in samadiyah (praying for the deceased) ritual practice. The community believes that the stones used in samadiyah ritual will relieve the corpse from the torment of the grave. The reading of samadiyah using stone media as a calculating tool is the community’s response to the Qur’anic texts interpreted in everyday life. This research aims to find out how the history of the tradition and the practice of stone media as wasilah in samadiyah ritual practice in Peulokan village, West Labuhan Haji, South Aceh. This research used a qualitative approach. The techniques of data collection utilized in this research were observation, interviews, and documentation. The results of the study show that the practice of wasilah with stone media in samadiyah ritual was performed whenever people passed away. The use of stones as media in samadiyah ritual is one of the Sufism teachings, which is also practiced by khatam khawaja or khatam tahlil in suluk and the other basis that is used as a reference in this practice which is recommended by the Prophet Muhammad PBUH. The practice of reciting samadiyah in Peulokan village, West Labuhan Haji, South Aceh is relatively the same as in other places. The only differences are the increased number of surah Al-Ikhlas and stones used as media for counting. Abstrak: Tradisi wasilah yang di lakukan masyarakat Gampong Peulokan, Labuhan Haji Barat Aceh Selatan berbeda dengan yang lainnya, yaitu mempraktikkan ritual samadiyah dengan media batu sebagai wasilah. Masyarakat memiliki kepercayaan bahwa batu-batu yang diikutsertakan dalam samadiyah akan melepas kesengsaraan mayit dalam kubur. Pembacaan samadiyah dengan menggunakan batu sebagai media hitung, merupakan respon masyarakat terhadap teks Al-Qur’an yang dijumpai dalam kehidupan. Penelitian ini bertujuan untuk mengetahui bagaimana sejarah tradisi dan praktik penggunaan batu sebagai wasilah pada samadiyah kematian di Desa Peulokan, Labuhan Haji Barat, Aceh Selatan. Penelitian ini merupakan jenis penelitian lapangan dengan menggunakan pendekatan kualitatif. Sedangkan teknik pengumpulan data yang digunakan dalam penelitian ini adalah teknik observasi, wawancara serta dokumentasi. Hasil penelitian di dapatkan bahwa praktik tradisi wasilah dengan media batu pada samadiyah dilakukan setiap ada kematian. Penggunaan Media Batu dalam samadiyah kematian merupakan salah satu ajaran tasawuf yang juga dipraktikkan pada khatam khawaja atau khatam tahlil pada sulok dan dasar lainnya yang di jadikan sebagai acuan dalam praktik tersebut adalah anjuran dari Rasulullah saw. Praktik pembacaan samadiyah di Gampong Peulokan, Labuhan Haji Barat Aceh Selatan relatif sama dengan di tempat lain, perbedaannya pada jumlah bacaaan surah al-Ikhlaṣ diperbanyak dan memakai batu sebagai media hitungnya
Keywords: Wasilah; Stones as Media; Samadiyah